Redox System and Oxidative Stress-Targeted Therapeutic Approaches in Bladder Cancer - George J. Dugbartey; Sydney Relouw; Liam McFarlane; Alp Sener (Antioxidants, 2024)
Bladder cancer (BCa) is the most common genitourinary malignancy, with a high global incidence and recurrence rate that is paired with an increasing caregiver burden and higher financial cost, in addition to increasing morbidity and mortality worldwide. Histologically, BCa is categorized into non-muscle invasive, muscle invasive, and metastatic BCa, on the basis of which the therapeutic strategy is determined. Despite all innovations and recent advances in BCa research, conventional therapies such as chemotherapy, immunotherapy, radiotherapy, and surgery fall short in the complete management of this important malignancy. Besides this worrying trend, the molecular basis of BCa development also remains poorly understood. Burgeoning evidence from experimental and clinical studies suggests that oxidative stress resulting from an imbalance between reactive oxygen species (ROS) generation and the body’s antioxidant production plays an integral role in BCa development and progression. Hence, ROS-induced oxidative stress-related pathways are currently under investigation as potential therapeutic targets of BCa. This review focuses on our current understanding regarding ROS-associated pathways in BCa pathogenesis and progression, as well as on antioxidants as potential adjuvants to conventional BCa therapy.